KEWENANGAN DEWAN KEHORMATAN PENYELENGGARA PEMILU (DKPP) DALAM MENYELESAIKAN PELANGGARAN PEMILIHAN KEPALA DAERAH TAHUN 2015 OLEH ANGGOTA KOMISI PEMILIHAN UMUM KABUPATEN KAPUAS HULU - MUHAMMAD RESKY RIZAL, S.I.K NPM. A2021151083, JURNAL MAHASISWA S2 HUKUM UNTAN (Jurnal NESTOR Magister Hukum, 2017)
Abstract This thesis discusses the Honor Council Election Authority (DKPP) Resolving Violations In local elections in 2015 by members of the Election Commission Kapuas Hulu. This study uses normative legal research methods, through the study of literature and sociological research methods .. From the results of this thesis can be concluded that Resolution Process By Law for Violations of the Code by a member of the Election Commission Kapuas Hulu. DKPP's duty and authority is the Decision. In accordance with the domain of DKPP authority, DKPP's Decision is in the form of sanction or rehabilitation. Determination of this Decision taken in a closed DKPP plenary meeting. DKPP plenary will decide when the examination in the trial have been considered sufficient examination of complaints, listen to the defense and the witnesses, and considering the evidence / written documents, and studied the evidence and the evidence is included. The principle of ethical judiciary developed is that all people are heard (audi et alteram partum). Sanctions that can be issued by DKPP are in the form of Written Reprimands, Dismissal and Fixed Termination or dismissal. Implementation Authority DKPP (Honor Council Election) in resolving violations of the election by the members of the Election Commission Kapuas Hulu based on Law Number 15 Year 2011 regarding the General Election Organizer Honorary Council Election (DKPP) decided KPU and Panwaslu Kapuas Hulu guilty. Both institutions are considered to violate the code of ethics in the implementation of Election of Regional Head Election (Pilkada) in Kapuas Hulu District 2015 ago. DKPP impose sanctions in the form of Warning Loud and Dropping sanctions in the form of warning to the KPU and Panwaslu Kapuas Hulu.